Desenvolvimento tecnológico por origem de capital: A experiência brasileira recente - Graziela Ferrero Zucoloto; José Eduardo Cassiolato (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper discusses the impacts of the technological internationalization process in the Brazilian economy, focusing on R&D activities, comparing national and subsidiaries R&D performance. After a literature review, the paper presents the statistical profile of US multinational companies, analyzing if Brazil is attracting these investments. In detail, it compares R&D activities of national and subsidiaries firms in Brazil; statistical tests identify the importance of origin of capital in Brazilian R&D performance.
Keywords: O30; 330; Forschung; Technologietransfer; Brasilien